2003
DOI: 10.1246/cl.2003.886
|View full text |Cite
|
Sign up to set email alerts
|

Photochemical merfac One-way Isomerization of Phosphorescent Material. Studies by Time-resolved Spectroscopy for Tris[2-(4′,6′-difluorophenyl)pyridine]iridium(III) in Solution

Abstract: Photochemical characterization is reported for the mer-stereoisomer of fac-tris[2-(4′,6′-difluorophenyl)pyridine]iridium(III) (2), which has attracted attention as a electrophosphorescent material. The mer-2 has a much smaller emission-quantum yield and a shorter emission lifetime than those of the fac-isomer. The relation of the photophysical properties of mer-2 and one-way photoisomerization to fac-2 is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
47
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(52 citation statements)
references
References 16 publications
4
47
1
Order By: Relevance
“…The current result also agrees with previous reports for the related homoleptic Ir III metal complexes such as mer-and fac-[Ir-A C H T U N G T R E N N U N G (dfppy) 3 ], ((dfppy)H = 4,6-difluorophenyl pyridine), in which the meridional isomer is always less emissive at room temperature compared with its facial counterpart under identical conditions. [31] We believe that a similar electrontransfer process is operative for mer-[IrA C H T U N G T R E N N U N G (dfppy) 3 ], which induces a rapid radiation-free deactivation pathway, giving poor emission at room temperature. We thus expect that the interplay between T ILCT to T LLCT may, in general, play a key role for spectroscopy and dynamics of the homoleptic-me-A C H T U N G T R E N N U N G ridA C H T U N G T R E N N U N G ional types of transition-metal complexes.…”
Section: Resultsmentioning
confidence: 98%
“…The current result also agrees with previous reports for the related homoleptic Ir III metal complexes such as mer-and fac-[Ir-A C H T U N G T R E N N U N G (dfppy) 3 ], ((dfppy)H = 4,6-difluorophenyl pyridine), in which the meridional isomer is always less emissive at room temperature compared with its facial counterpart under identical conditions. [31] We believe that a similar electrontransfer process is operative for mer-[IrA C H T U N G T R E N N U N G (dfppy) 3 ], which induces a rapid radiation-free deactivation pathway, giving poor emission at room temperature. We thus expect that the interplay between T ILCT to T LLCT may, in general, play a key role for spectroscopy and dynamics of the homoleptic-me-A C H T U N G T R E N N U N G ridA C H T U N G T R E N N U N G ional types of transition-metal complexes.…”
Section: Resultsmentioning
confidence: 98%
“…The addition of a third cyclometallating ligand results in tris-cyclometallated Ir III complexes (path b). With cautious control of the reaction conditions, the kinetically preferred meridional (mer) or the thermodynamically favored facial (fac) isomers are accessible; homoleptic, [22][23][24] as well as heteroleptic ones, [25][26][27][28] have been obtained with high selectivity. It has been shown that in solution, applying thermal or photochemical energy, mer-isomers can be converted into the fac-form (path c).…”
Section: Progress Reportmentioning
confidence: 99%
“…Although several reports on the preparation of mer isomers have recently appeared for iridium complexes, their photochemical properties remains unclear. [6,7] Among them, we are interested in tris(1-phenylpyrazolato,N,C 2Ј )-iridium(III) [Ir(ppz) 3 , Scheme 1], as both the mer and fac isomers give no phosphorescence in solution at ambient temperature. [6,7] The main reason for this was reported to be the location of the thermally equilibrated nonradiative excited state just above the emissive state, [8,9] and the absence of phosphorescence from the mer isomer is partly due to the merǞfac geometrical isomerization.…”
Section: Introductionmentioning
confidence: 99%
“…[6,7] Among them, we are interested in tris(1-phenylpyrazolato,N,C 2Ј )-iridium(III) [Ir(ppz) 3 , Scheme 1], as both the mer and fac isomers give no phosphorescence in solution at ambient temperature. [6,7] The main reason for this was reported to be the location of the thermally equilibrated nonradiative excited state just above the emissive state, [8,9] and the absence of phosphorescence from the mer isomer is partly due to the merǞfac geometrical isomerization. [6,7] Ir(ppz) 3 is reasonably phosphorescent in the solid phase, and therefore, a blue-emitting OLED device has been fabricated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation